KONFLIK SOSIAL DAN MASALAH SOSIAL NASKAH DRAMA BUNGA SEMERAH DARAH KARYA W.S. RENDRA SERTA PEMANFAATANNYA SEBAGAI MEDIA AJAR TEKS DRAMA DI SMK - Nur Sulis Adi Nugroho; Budhi Setiawan (Universitas Batanghari, 2025)
This study aims to describe: (1) the forms of social conflict in the drama script “Bunga Semerah Darah” by W.S. Rendra, (2) the forms of social issues in the drama script “Bunga Semerah Darah” by W.S. Rendra, (3) the utilization of social conflict and social issues in the drama script “Bunga Semerah Darah” by W.S. Rendra as a teaching medium for drama texts at vocational high schools. This research is a qualitative descriptive study using a literary sociology approach. The data sources used in this study include the drama script titled Bunga Semerah Darah by W.S. Rendra, as well as informants consisting of Indonesian language teachers, media experts, and grade XI students. Sampling was conducted using purposive sampling. To collect data, document analysis, questionnaires, and interviews were used. Data validity was tested through theory and data source triangulation. Data analysis was conducted using a flowing analysis approach. The results of the study showed several findings as follows. First, there were 22 findings of social conflict dialogue contained in the drama script Bunga Semerah Darah by W.S. Rendra. These forms of social conflict are a) gender conflict, b) conflict of interest, c) intergroup conflict, and d) interpersonal conflict. Second, there were 20 findings of dialogue forms of social problems contained in the play Bunga Semerah Darah by W.S. Rendra. These social issues are a) poverty, b) crime, c) family disorganization, d) violation of social norms, e) the environment, and f) bureaucracy. Third, the findings were utilized in Indonesian language learning as a teaching medium for drama texts. Its use as a teaching medium has been validated by research informants, so that the social conflicts and social issues in the play Bunga Semerah Darah by W.S. Rendra are appropriate and suitable for use as a teaching medium for drama texts in vocational high schools.